SAT0344 The Association Between Cumulative Glucocorticoid Exposure and Glucocorticoid-Related Adverse Events Among Patients with Rheumatoid Arthritis: A US Database Analysis. (9th June 2015) - Best, J.H.; Farr, A.; Sarsour, K.; Stott-Miller, M.; Hwang, Y.
Abstract : Background: Oral glucocorticoids (OGCs) are commonly used to treat inflammation associated with rheumatoid arthritis (RA). The appropriate duration of use and dose is debated because of the adverse event (AE) profile of OGCs. Objectives: To evaluate the associations between cumulative doses of OGCs and OGC-related AEs among patients with RA. Methods: RA patients 18 years of age and older were selected from a large US administrative claims database based on the presence of ≥2 claims with a diagnosis code for RA in 2012. RA patients were required to be continuously enrolled in the database from January 1, 2012, to December 31, 2012 (baseline period) and from January 1, 2013, to December 31, 2013 (evaluation period) and could not have received a diagnosis for another autoimmune condition. Cumulative OGC dose was measured in outpatient pharmacy claims during the baseline period. The presence of an OGC-related AE (diagnosis of osteoporosis, bone fracture, aseptic necrosis of the bone, cataract, diabetes, or ulcer/gastrointestinal hemorrhage in the inpatient or outpatient setting or diagnosis of pneumonia, opportunistic infection, myocardial infarction, or stroke during an inpatient admission) was assessed during the evaluation period. Multivariable logistic regression models were fitted to compare odds of OGC-related AEs across levels of cumulative doses of OGC, controlling for patient demographic and clinical characteristics. Models were stratified by use of disease-modifying antirheumatic drugs in the baseline period. Results: The sample was composed of 84, 357 RA patients; mean age was 59 years, and 76% were female; 48% used OGCs during the baseline period, with a mean cumulative dose of 1, 334 mg (median, 770 mg). During the follow-up period, 22, 207 patients (26%) had an OGC-related AE. The most common AEs were cataract, bone fracture, and osteoporosis. Table 1 displays the number of patients with an AE for each OGC dose cohort and the adjusted odds ratio for AEs (95% CI), with the no-OGC use cohort as the reference group. Conclusions: Among RA patients, those with a cumulative OGC dose of >1, 800 mg during a 12-month period generally had a greater probability of experiencing an OGC-related AE during the following year. A cumulative dose between >800 and 1, 800 mg was associated with an increased probability of bone fracture and osteoporosis. Disclosure of Interest: J. Best Employee of: Genentech, A. Farr Consultant for: Genentech, K. Sarsour Employee of: Genentech, M. Stott-Miller Consultant for: Genentech, Y. Hwang: None declared